Peranan Guru Pendidikan Agama Islam Dalam Meningkatkan Kedisiplinan BeribadahSiswa Kelas VII di SMPN 21 Tompobulu Kab. Maros - Nofia Syahidah; Rusli Malli; Ahmad Abdulloh (Yayasan Al-Afif, 2025)
This study aims to: (1) Obtain a clear overview of the role of Islamic ReligiousEducation (IRE) teachers in improving students' discipline in worship in GradeVII at UPTD SMPN 21 Tompobulu, Maros Regency; (2) Determine the resultsof students’ level of worship discipline in Grade VII at UPTD SMPN 21Tompobulu, Maros Regency; and (3) Identify the inhibiting factors inimproving students’ discipline in worship in the same context.This researchemploys a field research method, in which data is collected directly at theresearch site. The approach used is qualitative descriptive, with data collectiontechniques including observation, documentation, and interviews with theschool principal, Islamic Religious Education teachers, guidance andcounseling teachers, and Grade VII students at UPTD SMPN 21 Tompobulu,Maros Regency.The findings reveal that Islamic Religious Education teachersplay a crucial role in developing students’ habits and discipline in performingprayer (shalat). Teachers not only deliver theoretical materials through lecturesbut also guide students directly through practical sessions, habituation, andsupervision of prayer implementation at school. The IRE teachers alsocollaborate with homeroom teachers and the principal to monitor students whoare undisciplined in performing their prayers. The level of students’ prayerdiscipline at school has shown improvement, especially under teachersupervision. However, this discipline has not fully extended to the homeenvironment. Some students still delay prayers or fail to perform them on timedue to a lack of parental supervision. This highlights the importance of theparents' role in shaping students’ prayer discipline outside of school. Severalobstacles are also faced by IRE teachers, including students’ low awareness ofpraying independently, negative influences from family and peers, and limitedfacilities such as a prayer room (musholla) that cannot accommodate allstudents and insufficient ablution (wudhu) areas.